PEMBUKUAN AKUNTANSI SEDERHANA PADA USAHA KECIL MENENGAH PAYUNG LUKIS NGUDI RAHAYU - Atika Jauharia Hatta; Toyibah Kusumawati; Muhammad Sabandi; Algifari Algifari; Wisnu Pajogo Algifari; Bhakti Nur Istiqomah Algifari (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Simple accounting bookkeeping training for small and medium enterprises (SMEs) through the community partnership program aimed at improving the ability of SME partners in managing their business financial bookkeeping. So far, SMEs have never used bookkeeping to record all transactions related to their business income or expenses, so it is difficult for them to know exactly how much profit they will get from their business. Through this community partnership program, devotees try to provide the simplest bookkeeping training in an effort to equip partners to be able to manage their finances better. The results obtained from this training are increased knowledge and skills of SMEs in making simple bookkeeping so that they can increase the motivation in running their business.